ASIAN INFRASTRUCTURE INVESTMENT BANK’S ROLE IN BUILDING SUSTAINABLE INFRASTRUCTURE IN THE MANDALIKA SPECIAL ECONOMIC ZONE TO ACHIEVE SUSTAINABLE DEVELOPMENT GOALS IN CENTRAL LOMBOK, WEST NUSA TENGGARA - Sirwan Yazid Bustami; Kurnia Zulhandayani Rizki; Hasbi Asyidiqi; Mega Nisfa Makhroja (ASIAN PUBLISHER, 2025)
The research aims to examine the role and contribution of the Asian Infrastructure Investment Bank (AIIB) in building sustainable infrastructure in the Mandalika Special Economic Zone (Mandalika SEZ) to meet sustainable development goals in Central Lombok, West Nusa Tenggara. It uses a qualitative approach with an analytical descriptive method. The research process was carried out through several stages, namely data collection, data reduction, data presentation, and conclusion drawing. Data collection was obtained through interviews and a literature study. Meanwhile, data reduction was conducted by reviewing the data collected to be selected in accordance with the research topic. Furthermore, the data presentation was performed in a narrative form. Finally, conclusion drawing was carried out according to elaboration of the concepts of multilateral development banks (MDBs), sustainable infrastructure, and sustainable development goals (SDGs). Based on the research results, AIIB has a key role in sustainable infrastructure development in Mandalika SEZ in terms of financing infrastructure development, providing technical assistance, and enhancing the management capacity of infrastructure development. Through its roles, AIIB contributes to achievement of a sustainable infrastructure development in the Mandalika SEZ. The achievement of a sustainable infrastructure development is influenced by a number of factors, namely effective public participation and consultation; alignment of project objectives with stakeholder needs; transparency and responsible decision-making mechanisms; adequate compensation and resettlement policies; green technology innovation; and government support, green incentive policies, and training programs. AIIB’s role in a sustainable infrastructure development has an impact on achieving the goals of the SDGs development pillars including social development pillar, environmental development pillar, economic development pillar, and law and governance development pillar.